Digital Literacy Training for Al-Khoir Foundation Teachers in Welcoming Innovative Education to Improve Technology-Based Learning - Sondari, Endang; Supadi, Supadi; Hamidah, Nur (Universitas Indraprasta PGRI, 2025)
The digital literacy training for teachers of the Al-Khoir Foundation aims to improve teachers' digital competencies in facing the challenges of innovative education and technology-based learning. The training methods used include providing online and offline materials on the basics of digital literacy, as well as relevant educational technology applications. In addition, the training also includes simulations and group discussions to explore the application of technology in effective learning. Participants were also allowed to conduct hands-on practice using various digital platforms to improve interaction and teaching skills. The results of this training show a significant increase in the understanding and application of technology in the learning process by teachers. The contribution of this training is to strengthen teachers' readiness to welcome innovative technology-based education, supporting the creation of more effective and interesting learning for students.